Hak Kebendaan dan Keabsahan Perjanjian Kebendaan Virtual Land di Dalam Metaverse Ditinjau Berdasarkan KUHperdata - Sandi Pratama Putra Bali (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
Virtual land assets in the metaverse are becoming popular and have high investment potential. In Indonesia, virtual land is a new object in property law, and this object has not been regulated yet by positive law. This study aims to identify the legal position of virtual land in the context of material rights and the validity of material agreements in trading a virtual land asset on the metaverse platform according to the Indonesian Civil Code (KUHPerdata). The research method used is normative-juridical using secondary data. Based on the research results, it concludes that virtual land can be classified as an intangible movable object and can be attached to property rights. From the transaction’s validity, the Civil Code views virtual land transactions as asset exchange agreements, which are legal and recognized transactions based on positive Indonesian law